Comparative antibacterial activity of clove extract against Pseudomonas aeruginosa - Deniz M. Al-Tawalbeh; Jafar M. Alawneh; Waleed Momani; Amal Mayyas (BMC Complementary Medicine and Therapies)
Abstract Pseudomonas aeruginosa is an opportunistic pathogen belonging to the γ-proteobacteria family, known to cause pneumonia linked with ventilator use and nosocomial infections. With the increasing prevalence of antibiotic-resistant bacteria, there is a pressing need to identify alternatives to conventional antibiotics. Plant-derived substances (PDSs) offer potential not only as antibacterial agents but also as modulators of antibiotic resistance. In this study, diffusion assay using disc agar, and the minimum inhibitory concentration (MIC) assay of each imipenem, amoxicillin-clavulanic acid, and clove extract was determined. The clove extract was analyzed via the UHPLC/MS, and the checkerboard assay was employed to evaluate the potential synergistic effects of combining clove extract with both antibiotics. The combination of clove extract to each antibiotic led to a significant reduction in their respective MICs. Moreover, each antibiotic exhibited synergistic effects on the fractional inhibitory concentration value (FIC) of clove extract. The analysis identified seventeen components in the clove extract, predominantly flavonoids and phenolic compounds. The antibacterial efficacy of the Syzygium aromaticum Myrtaceae extract against P. aeruginosa indicated its potential as a promising antibacterial agent capable of enhancing the effectiveness of existing medications.